Computational Profiling of Sapindus rarak (Lerak) Phytochemicals as Potential Antibacterial and Immunomodulatory Agents against Escherichia coli - Lisa Savitri; Kharisul Ihsan; Elfred Rinaldo Kasimo; Rochmad Krissanjaya (Biology, Medicine, & Natural Product Chemistry, 2026)
Antibiotic resistance in Escherichia coli continues to rise, creating an urgent need for new antibacterial candidates with novel mechanisms of action. Sapindus rarak contains diverse phytochemicals, including saponins, flavonoids, and triterpenoids, yet the molecular basis of their biological activity remains poorly understood. This study aimed to profile the antibacterial and immunomodulatory potential of major S. rarak compounds using a computational approach. Twenty phytochemicals were collected from public databases and evaluated against three targets: E. coli DNA gyrase and DHFR, and human TLR4. Docking analysis identified rarasaponin A and B as the strongest gyrase binders, with binding energies of -9.8 and -9.6 kcal/mol. A 100-ns molecular dynamics simulation demonstrated stable interactions between rarasaponin A and gyrase, supported by consistent RMSD values and an MM–GBSA energy of approximately -42 kcal/mol. Flavonoids such as quercetin-3-O-glucoside showed preferential binding to TLR4 and were predicted to promote IL-10 induction with minimal TNF-alpha activation. ADMET predictions indicated more favorable pharmacokinetic properties for flavonoids than saponins. These findings support a dual-mechanism therapeutic model in which saponins act as antibacterial agents and flavonoids contribute to balanced immune modulation. Further experimental validation through in vitro and in vivo assays is recommended.